Systemic Immune Modulation in Gliomas: Prognostic Value of Plasma IL-6, YKL-40, and Genetic Variation in YKL-40 - Holst, Camilla Bjørnbak; Christensen, Ib Jarle; Skjøth-Rasmussen, Jane; Hamerlik, Petra; Poulsen, Hans Skovgaard; Johansen, Julia Sidenius (Frontiers in Oncology, 2020)
Background: Complex local and systemic immune dysfunction in glioblastoma (GBM) may affect survival. Interleukin (IL)-6 and YKL-40 are pleiotropic biomarkers present in the tumor microenvironment and involved in immune regulation. We therefore analyzed plasma IL-6, YKL-40 and genetic variation in YKL-40 and explored their ability to distinguish between glioma subtypes and predict survival in GBM. Methods: 158 patients with glioma WHO grade II-IV were included in the study. Plasma collected at surgery was analyzed for IL-6 and YKL-40 (CHI3L1) by ELISA. CHI3L1 rs4950928 genotyping was analyzed on whole-blood DNA. Results: Neither plasma IL-6 nor YKL-40 corrected for age or rs4950928 genotype could differentiate GBM from lower grade gliomas. GC and GG rs4950928 genotype were associated with lower plasma YKL-40 levels (CC vs. GC, p=0.0019; CC vs. GG, p=0.01). Only 10 and 14 out of 94 patients with newly diagnosed GBM had elevated IL-6 or YKL-40, respectively. Most patients received corticosteroid treatment at time of blood-sampling. Higher pretreatment plasma IL-6 was associated with short overall survival (OS) (HR=1.19 (per 2-fold change), p=0.041) in univariate analysis and YKL-40 showed a similar trend (HR=1.20 (per 2-fold change), p=0.056). The effect disappeared in multivariate analysis. rs4950928 genotype did not associate with OS (HR=1.30, p=0.30). In recurrent GBM, higher YKL-40 (HR=2.12 (per 2-fold change), p=0.0005) but not IL-6 (HR=0.99 (per 2-fold change), p=0.92) were associated with short OS in univariate analysis. Conclusion: In recurrent GBM high plasma YKL-40 may hold promise as a prognostic marker. In newly diagnosed GBM perioperative plasma IL-6, YKL-40 and genetic variation in YKL-40 did not associate with survival. Corticosteroid use may complicate interpretation of results.